AWARENESS, RISK PERCEPTION AND PRACTICE OF SELF-MEDICATION AMONG PREGNANT WOMEN ATTENDING ANTE-NATAL CLINICS IN SOKOTO, NIGERIA - Attahiru, Aisha; Awosan, K. Joseph; Hassan, Mairo; Arisegi, S. Adeniyi (Journal of Drug Delivery and Therapeutics, 2018)
Background: In addition to its adverse health effects on mother and fetus, self-medication is believed to be one of the main driving forces behind the increasing burden of antimicrobial resistance worldwide. This study aimed to assess the awareness, risk perception and practice of self-medication among pregnant women attending ante-natal clinics in Sokoto, Nigeria. Materials and Methods: A cross-sectional study was conducted among 315 pregnant women (selected by a two-stage sampling technique) attending the antenatal clinics of the Primary Healthcare Centres in Sokoto metropolis, Nigeria. Data were collected with a set of pretested, interviewer-administered, structured questionnaire. Data analysis was done using IBM SPSS version 20 statistical package. Results: Whereas, almost all the respondents (98.4%) were aware of self-medication, less than half of them (47.3%) perceived it as a serious threat to their health and the health of their unborn baby. Majority of respondents (67.9%) had self-medicated, with the most commonly self-medicated drugs being analgesics/antipyretics (35.1%), antimalarials (31.3%) and antibiotics (24.3%). The most commonly cited reasons for self-medicating were financial problems (28.5%), lack of the required drugs in the hospital (16.8%), lack of time (12.6%), and sickness being mild (9.8%). Self-medication practice was influenced by respondents’ age, marital status, educational background and perception of risk. Conclusion: This study showed low risk perception and high prevalence of self-medication among pregnant women in Sokoto, Nigeria. Sensitization of members of the public on the hazards of self-medication, poverty alleviation, and provision of comprehensive healthcare services at subsidized prices for pregnant women are hereby suggested. Keywords: Awareness, risk perception, practices, self-medication, pregnant women